Implementing Digital Literacy in Developing Learners’ Creative English Reading Skills at Inclusive Classrooms of Ibtidaiyah Madrasah (Conference on English Language Teaching, 2023)
The ongoing pandemic era has contributed to the application of digital literacy in learning English as a foreign language, including at the elementary school level. Students in the inclusive class also find it useful. The purpose of this study is to describe and analyze the implementation of digital literacy in developing students' creative reading skills in English learning in the Inclusion class of Islamic elementary schools and their impact. This research method uses descriptive qualitative which is categorized in the regular inclusion class. The primary resource consisted of the headmaster and the teachers of the inclusion class. While secondary sources are in the form of various literature related to digital literacy, creative reading, teaching English as a foreign language, and inclusion classes. The result is that the implementation of digital literacy in the Inclusion class goes through 3 stages, namely: preparing digital media in the form of video, audio, and gadgets and compiling lesson plans, then implementing them online/offline/blended according to applicable regulations. The next stage is evaluation through short video/audio as well as study materials by the expert team of children with special needs. This implementation has a positive impact, namely the raising of social awareness from classmates of children with special needs. Meanwhile, the negative impact is the limitation of madrasahs requiring operational permits for inclusive classes from the Ministry of Religion. The addition of digitization media needs to be maximized so that it can be used for the English development of students as a whole